O grande mal no Cemitério dos Vivos: diagnósticos de epilepsia no Hospital Nacional de Alienados Grand mal seizures in the Cemetery of the Living: the diagnosis of epilepsy at Brazil's National Hospital for the Insane - Margarida de Souza Neves (História, Ciências, Saúde: Manguinhos, 2010)
O objetivo deste artigo é analisar, na perspectiva da história social do pensamento médico, artigos sobre epilepsia publicados na revista Arquivos Brasileiros de Psiquiatria, Neurologia e Medicina Legal em 1915 e 1918. Esses artigos, por um lado, permitem identificar algumas das aproximações da medicina brasileira de inícios do século XX em relação a essa síndrome, em especial a associação direta então estabelecida pela ciência médica entre a epilepsia e a propensão à violência e ao crime. Por outro lado, permitem esboçar histórias de vida de pacientes diagnosticados como 'epiléticos', cujas observações clínicas são relatadas. This study in the social history of medical thought analyzes the articles on epilepsy published in the journal Archivos Brasileiros de Psychiatria, Neurologia e Medicina Legal in 1915 and 1918. Through these texts, I identify some of the ways in which early twentieth-century Brazilian medicine addressed this syndrome, particularly the direct association that medical science then drew between epilepsy and a propensity to violence and crime. The texts, which contain clinical observations on patients diagnosed as epileptics, also afford us a brief glimpse into these individuals' life stories.